2001
DOI: 10.1046/j.1439-0507.2001.0626.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of terbinafine in the eradication of Microsporum canis from laboratory cats

Abstract: In this study, the coats of 20 cats with no dermatophytosis lesions were sampled for colonization by Microsporum canis, which was isolated in 45% of cases. All cats were treated with oral terbinafine for 3 weeks. The drug was administered orally at a daily dosage 8.25 mg kg-1. Mycologic status was assessed at the end of the treatment; and after follow-up at 2 days, and 4 and 9 weeks. The final evaluation revealed a complete mycologic cure of all cats by obtaining negative cultures, thereby demonstrating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…In another study, low doses of terbinafine (8.25 mg/kg/day for 21 days) were effective for eradication of M. canis spores from the haircoat of asymptomatic carrier cats (Castanon‐Olivares et al ., 2001).…”
Section: Terbinafinementioning
confidence: 99%
“…In another study, low doses of terbinafine (8.25 mg/kg/day for 21 days) were effective for eradication of M. canis spores from the haircoat of asymptomatic carrier cats (Castanon‐Olivares et al ., 2001).…”
Section: Terbinafinementioning
confidence: 99%
“…After a number of studies in animals, scientists have proved that orally administered terbinafine is effective in the treatment of cats suffering from experimentally induced or naturally occurring dermatophytosis (Castanon-Olivares et al 2001, Kotnik 2002, Kotnik and Cerne 2006, Foust et al 2007). Recently topically applied terbinafine showed superior effectiveness in the treatment of experimental M. canis infection in guinea pigs (Ivaskiene et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Krafchik (1997) suggested that higher doses might shorten the therapy course. The second study on use of terbinafine in cats (Castanon-Olivares et al 2001) was done on a group of asymptomatic carriers. The dose of 8.25 mg/kg QD was effective in elimination of the colonization, but might be insufficient to resolve an experimental infection, in our opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Terbinafine has been used in animals mostly during pre-clinical studies (Mieth and Petranyi 1989). Only few reports were found of the drug currently being used in cats (Mala 1995;Mancianti et al 1999;Castanon-Olivares et al 2001). The purpose of our study was to follow the efficacy of terbinafine hydrochloride (Lamisil ® , Novartis) in the treatment of cats experimentally infected with M. canis.…”
mentioning
confidence: 99%